METHODOLOGY OF MAKING MENTALLY RETARDED CHILDREN INTERESTED IN LESSONS (Academia Science Repository, 2023)
Childhood is a valuable period in a person's life, which determines his future development prospects. The foundation laid in a relatively short period of life is of great importance for the entire further development of the child. The issue of comprehensive development of intellectual, cognitive and creative abilities of preschool children remains one of the most urgent issues today. Every year, the surrounding world, into which the child enters, sets more and more complex tasks, to solve them it is not enough to see, hear, feel, but it is important to emphasize the connections and relationships between events. The article talks about the advantages and disadvantages of using innovative and advanced foreign experiences in the educational process, as well as methods of teaching intellectually disabled children and raising their morale.